2009
DOI: 10.1245/s10434-009-0531-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD40 Targeting miR-224 and miR-486 on the Progression of Pancreatic Ductal Adenocarcinomas

Abstract: Epigenetic alterations with upregulated CD40-targeting miR-224 and miR-486 are related to downregulated CD40 protein expression at cell surfaces in highly invasive and metastatic PDAC. Thus, miRNA-regulated CD40 expression seems to play an important role in progression of PDAC. These data suggest a diagnostic and therapeutic potential for CD40 and/or its targeting miRNAs in PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 44 publications
1
100
0
1
Order By: Relevance
“…miR-224 is reported to be overexpressed in various types of cancer (15)(16)(17)(18)(19)(20), and it plays critical roles in malignant phenotypes. Consistent with these previous observations, miR-224 was found to be upregulated in HepG2 cells in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-224 is reported to be overexpressed in various types of cancer (15)(16)(17)(18)(19)(20), and it plays critical roles in malignant phenotypes. Consistent with these previous observations, miR-224 was found to be upregulated in HepG2 cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of miR-224 has been reported in several human cancers (15)(16)(17)(18)(19). Wang et al found that miR-224 is upregulated in HCC patients and HCC cell lines (20), and promotes HCC cell apoptosis by targeting the transcript expression levels of apoptosis inhibitor 5 (API-5).…”
Section: Introductionmentioning
confidence: 99%
“…It should be also noted that these miRNAs have other predicted and experimentally validated targets. For example, miR-224 is up-regulated in highly invasion pancreatic ductal adenocarcinoma, and it is correlated with the down-regulation of CD40, which it is predicted to target (Mees et al, 2009). MiR-224 is also predicted to target apoptosis inhibitor-5 in hepatocellular carcinoma; it is found to be significantly up-regulated in hepatocellular carcinoma and as a result inhibits apoptosis and induces tumourigenesis .…”
Section: Discussionmentioning
confidence: 99%
“…miR-224 has been revealed to be upregulated in various types of tumor when functioning as an oncogene (79)(80)(81). Nevertheless, a previous study identified that miR-224 was downregulated in mucinous cystic neoplasms (MCNs) of the pancreas (81).…”
Section: Gastric Cancermentioning
confidence: 99%